PERANCANGAN KATALOG PRODUK PADA PERUSAHAAN IDCOCO INDONESIA - Laulita, Nasar Buntu; Karimah, Zulfiniar Nur (Universitas Madura, 2024)
The IDcoco Indonesia company, in running its business with a target market that already includes the international market, currently has various competitors because various companies have emerged that are engaged in the same field and sell similar products. Therefore it is very important to design marketing media, one of which is in the form of an attractive product catalog, which has more value and is effective for potential customers to make it easier for them to make purchasing decisions for IDcoco Indonesia products. Qualitative methods and primary data from interviews with informants and secondary data from previous studies are used as the basis for information in the designed product catalog. The results of the catalog design that has been carried out can finally provide detailed information regarding product descriptions, specifications, production capacity and shipping procedures and are presented with attractive visualizations using English as an international language so that the information presented can make it easier for potential customers both from within the country and abroad countries to make purchasing decisions for IDcoco Indonesia products.